(untitled) (Research, Society and Development, 2022)
Introduction: The audit aims to control costs, quality of patient care, fair payment of the hospital bill, transparency of negotiation. In nursing, auditing is an activity dedicated to the effectiveness of services. Healthcare-associated infections acquired during healthcare provision are examples of adverse events that impact the quality of services provided. Objective: To describe the role of nurses in the hospital audit on the control of infections related to care in health. Methodology: This is a study with a qualitative approach, of the integrative review type, where health auditing on the control of infections related to health care will be addressed. It was carried out by searching a database available in the Virtual Health Library (VHL) through the health descriptors: nurses, infections related to health care and nursing audit, in Portuguese, respecting the 5-year time frame (2019- 2022). Results: For the development of the study, readings and detailed analyzes of five documents found from the search carried out previously were carried out. Final Considerations: Infections related to health care are just one of the many aspects relevant to health auditing, they represent low quality in health care. The nurse auditor is part of a need for the health institution, monitoring how the records are being carried out, having a critical and proposing view, performing their attributions aimed at improving and quality in care and the reduction of losses.